(untitled) (Baghdad Science Journal, 2025)
In this work, the synergistic effect of chlorinated rubber (additive I),with zeolite 3A (additive II), zeolite 4A (additive III), and zeolite 5A (additive IV) in (1:1) weight percentage, on the flammability for unsaturated polyester resin was studied in the weight ratios for (3,7,10,13&15%) by preparing films of (130×130×3) mm in diameters. Three standard test methods used to measure were the flame retardation which are; ASTM: D-2863, ASTM: D- 635& ASTM: D-3014. Results obtained from these tests indicated that all of the additives were effective additive IV has the highest efficiency as a flame retardant.